Developmental obstacles adversely affecting emerging contractors in the construction industry of Limpopo province - Zeleke Worku (Problems and Perspectives in Management, 2016)
This study attempts to identify and quantify factors that adversely affect the growth and development of emerging contractors in the construction industry of Limpopo Province in South Africa. The study is based on a stratified random sample of 229 emerging contractors who operate in the construction industry of Limpopo Province. The degree of entrepreneurial skills in emerging contractors was assessed by using a composite index defined by Beck and Demirguc-Kunt (2012). Quantitative and qualitative research methods were used for data collection and analysis. The study found that 139 of the 229 emerging contractors selected for the study (60.70%) lacked entrepreneurial skills by the standards of Beck and Demirguc-Kunt (2012), whereas 90 of them (40.18%) had adequate entrepreneurial skills by the same standards. The study also showed that 141 of the 229 emerging contractors in the study (61.57%) lacked basic skills in construction engineering. More than half of the contractors in the study had disadvantaged backgrounds in terms of technical and entrepreneurial skills as well as capital and access to finance. The study found that 122 of the 229 emerging contractors (53.28%) were viable financially while the remaining 107 emerging contractors (46.72%) were not viable financially. Results obtained from the study showed that viability in emerging contractors was significantly influenced by barriers such as lack of construction engineering skills, lack of entrepreneurial skills, lack of access to finance, inability to network with well-established contractors, inability to draw up business plans, and delay in payment for services rendered, in a decreasing order of strength. Keywords: construction industry, emerging contractors, Limpopo Province. JEL Classification: C5, M21